Separability of Algebras (Mini-course given at the Dokuz Eylul University, Izmir (Turkey)) - Christian Lomp (2008)
Mini-course on separable algebras giving for Turkish students at the Dokuz Eylul University in Izmir (Turkey) as part of the LLP/Erasmus Agreement.